Β-1, 3-glucan-lacking Aspergillus fumigatus mediates an efficient antifungal immune response by activating complement and dendritic cells. Issue 1 (1st January 2019) - Steger, Marion; Bermejo-Jambrina, Marta; Yordanov, Teodor; Wagener, Johannes; Brakhage, Axel A; Pittl, Verena; Huber, Lukas A; Haas, Hubertus; Lass-Flörl, Cornelia; Posch, Wilfried; Wilflingseder, Doris
ABSTRACT: Complement system and dendritic cells (DCs) form – beside neutrophils and macrophages – the first line of defense to combat fungal infections. Therefore, we here studied interactions of these first immune elements with Aspergillus fumigatus lacking ß-1, 3-glucans ( fks1tetOn rep under repressed conditions) to mechanistically explain the mode of action of echinocandins in more detail. Echinocandins are cell wall active agents blocking β-glucan synthase, making the A. fumigatus fks1tetOn mutant a good model to study immune-modulatory actions of these drugs. We now demonstrate herein, that complement was activated to significantly higher levels by the fks1- deficient strain compared to its respective wild type. This enhanced covalent linking of complement fragments to the A. fumigatus fks1tetOn rep mutant further resulted in enhanced DC binding and internalization of the fungus. Additionally, we found that fks1tetOn rep induced a Th1-/Th17-polarizing cytokine profile program in DCs. The effect was essentially dependent on massive galactomannan shedding, since blocking of DC-SIGN significantly reduced the fks1tetOn rep - mediated induction of an inflammatory cytokine profile. Our data demonstrate that lack of ß-1, 3-glucan, also found under echinocandin therapy, results in improved recognition of Aspergillus fumigatus by complement and DCs and therefore not only directly affects the fungus by its fungistatic actions, but also is likely to exert indirect antifungal mechanisms by strengthening innate host immune mechanisms. Abbreviations : C: complement; CR:complement receptor; DC: dendritic cell; iDC: immature dendritic cell; DC-SIGN: Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin; ERK: extracellular signal–regulated kinases; JNK : c-Jun N-terminal kinases; MAPK: mitogen-activated protein kinase; NHS: normal human serum; PRR: pattern recognition receptor; Th :T helper; TLR :Toll-like receptor; WT: wild type.